Platelet-rich plasma strategy against freezing damage in ram spermatozoa: its effect on miRNA, ion channels, growth factors, lipids and oxidative stress - Gungor, Ibrahim Halil; Turk, Gaffari; Cihangiroglu, Aslihan Cakir; Arkali, Gozde; Tektemur, Ahmet; Ozmen, Gorkem Kirmizikaya; Cambay, Zafer (Csiro Publishing, 2025)
Context Platelet-rich plasma (PRP) is a plasma component containing high concentrations of platelets, growth factors, antioxidants and proliferative properties.Aim To mitigate the negative effects of cryopreservation on ram semen by utilising PRP.Methods Semen was collected from six rams twice a week for 3 weeks during the breeding season. Pooling was performed by dilution with tris + egg yolk diluent. Pooling was divided into three equal parts and re-diluted with diluents containing control (0% PRP), 5% PRP and 10% PRP. Sperms were frozen in an automatic freezing device and stored in liquid nitrogen. After thawing, spermatological, flow-cytometric, oxidative stress, cholesterol, fatty acid, ELISA, quantitative real-time polymerase chain reaction (qRT-PCR) and western blot analyses were performed.Key results Compared with the control group, the 5% PRP group exhibited a significant increase in progressive motility, viability and cholesterol ratios, glutathione-peroxidase activity, CATSPER1 (Cation Channel of Sperm), CATSPER3, vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF) levels and KCNJ11 (Potassium Channel, Inwardly Rectifying, Subfamily J, Member 11), HSA-MIR-181A, HSA-MIR-150 and HSA-MIR-374 transcripts. Apoptotic protein, malondialdehyde and HSA-MIR-410, OAR-MIR-10B, BTA-MIR-22-3P and RNO-MIR-494 transcripts were decreased in 5% PRP group compared with control. PRP supplementation at 10% increased dead sperm and heptadecenoic acid ratios, VEGF and PDGF levels and HSA-MIR-410, PPY-MIR-16, CFA-MIR-199, HSA-MIR-181A, HSA-MIR-150, OAR-MIR-127, HSA-LET-7A and HSA-MIR-374 transcripts as well as CATSPER3, HSD3 beta 2, PDGFB and VEGFA proteins compared with the control. PRP supplementation at 10% significantly decreased plasma membrane integrity, insulin-like growth factor 1 (IGF1) level and CATSPER3 and KCNJ11 transcripts compared with the control.Conclusions The addition of 5% PRP before cryopreservation has beneficial effects on the functional and molecular properties of frozen-thawed ram spermatozoa, whereas the addition of 10% PRP has negative effects.Implications Five per cent PRP should be added to ram semen diluents.
Keywords: flow cytometer; growth factors; ion channels; miRNA; oxidative stress expressions; platelet-rich plasma; Ram; semen freezing